“Identificación y control in vitro de enfermedades fungosas en semillas de maíz (zea mays), en el laboratorio de sanidad vegetal de la UNSM.” - Diaz Chuquizuta, Henry (2005)
Presently investigation work the. main causal agents were. isolated that cause the illnesses in the seed of com, being identified Rhyzoctonia solani, Diplodia maydis, Fusarium oxysporum, CuNularia intermediate and Fusarium moniliforme. Also the effect of 7 commercial fungicidas was evaluated about the growth miceliar of the mushrooms in study in a test in vitro, being considered contact products, systemic and compound, of those which, Tiofanate Metl + Thiram, Mancozeb, Mancozeb + Benomil and they Captan + Flutolanil inhibited in 100,00 % the development micelial. lt was found that all were efficient except Benomil for the control of CuNularia intermediate that 1 present a growth rnicelial in PDA óf'45,60 mm~ PrO'pineb forthe control of' Fusariumoxysporum that 1 presenta growth micelial in PDA of 38;80 mm, Fusarium.moniliforme that 1 presenta growth micelial in PDA 50.40 mm; Triadimenol far the control of Rhyzoctonia solani that 1 presenta growth micelial in PDA of 29,20 mm and Fusarium moniliforme obtaining a growth micelial in PDA of 10,60 mm. For · the patogenicidad test 1 am 'Clemonstrated that the mushrooms causing more harmful fitopatógenos of pudriciones in the seeds are Fusarium moniliforme 100,00%, Diplodia maydis 100,00%, Rhyzoctonia solani 91,80%, CuNularia íntermediate 87,80% and Fusarium oxysporum 83,80%. · In the · germination test with applications of fUngicides percentages of germination of the, were, obtained· (81,23% for Tiofanate Metil .+ Thiram), . . (81,17% for thf!Y Captan + Flutolanil), (79,32% for Benomil), (79,04% for 'Mancozeb + 'Benomil), (7s;o·g3 'for'Mancozeb) T78,1l4% ·toritiadimenol) and (77,00% forPropineb). Likewise for the germination percentage in function at the time (hours) percentages of 83,17% were obtained in 48 hours, 88,54% in 72 hours, 92,60% in 96 hours and 94,54% in 120 hours, showing a of uniform germination starting from the 120 hours - 168 hours.